IMPLEMENTATION OF THE WILGERODT-KINDLER REACTION OF 2-METHYL-6-NITROQUINAZOLIN-4-ONE (Scientific journal of the Fergana State University, 2026)
Quinazoline derivatives are of great theoretical and practical importance. Among them, biologically active substances for agriculture (fungicides, bactericides, insecticides, and many plant growth stimulants) have been discovered. For example, peganum is isolated from the harmala plant (bitter gourd). Synthetically isolated desozipeganine is used in medicine as an anticholinesterase agent. The presence of several active centers in the quinazoline thioamide molecule, including a thioamide group (C=S) in position 2, endocyclic and exocyclic nitrogen atoms in positions 1 and 3, The presence of a carbonyl group at position 4 and a benzene ring indicates that these compounds are capable of undergoing electrophilic and nucleophilic substitution reactions at one or more reaction centers. The study of the reactions of 2-methyl-6-nitroquinazolin-4-one and its thioamides is of great interest. In this article, reactions of 2-methyl-6-nitroquinazolin-4-one with thioamidating reagents under various conditions using a three-component catalytic method were carried out. The reaction was carried out in the presence of a mixture of reagents with dimethyl sulfoxide while heating on an oil bath. As a result of the reaction, thioamides of 6-nitroquinazolin-4-yl-2-thiocarboxylic acids were synthesized in high yields. A search based on literature data for numerous biologically active compounds from the obtained thioamides indicates the relevance of this work.